SILOGISME HIPOTESIS SEBAGAI DASAR RASIONAL DALAM PENGAMBILAN KEPUTUSAN MANAJEMEN DAKWAH - Romlah; Riniyati; Meity Suryandari (STKIP Subang, 2025)
This study explores the role of hypothetical syllogism as a rational foundation for decision-making in da’wah management. Through a library research approach, the study analyzes literature on logic, Islamic mantiq, rational decision-making models, and previous studies on da’wah management. The findings reveal that da’wah organizations in Indonesia often rely on intuitive or ad hoc decision-making processes, which limits accountability and evaluation. By applying hypothetical syllogism, normative premises derived from Islamic values can be systematically connected with empirical premises from the field, producing more transparent and accountable decisions. Moreover, integrating hypothetical syllogism with the bounded rationality framework allows decision-making to remain rational even under limited information, time, and resources. This study contributes theoretically by integrating classical logic with modern decision-making theories, methodologically by offering an audit protocol for reasoning in da’wah management, and practically by providing operational guidelines for da’wah institutions. Keywords: Hypothetical syllogism, decision-making, da’wah management, bounded rationality, Islamic logic